Rekonsepsi Komunikasi Gender dalam Al-Qur’an - Ellys Lestari Pambayun; Nasaruddin Umar (Dakwah Institut PTIQ Jakarta, 2022)
The aim of the study is to explore gender communication through understanding non-misogynistic interpretations so that a liberative, just and harmonious Muslim society is created. Based on qualitative research and literature studies on classical and contemporary interpretations, gender communication is generally described as having equal potential to become destructive or constructive behavior, both in private and public spaces. An interesting finding in this study is that, from the perspective of the Qur'an, each male and female communication character is described as having a binary opposition dimension – positive-negative, strong-weak, rational-emotional, subjective-objective, and private-public. which then became the trigger for debate from among the clergy to academics which had implications for the function and position of the two sexes on earth. The Qur'anic perspective on the area of gender communication in relation to acts of violence or discrimination, found comparisons and solutions in two communication cues, namely: a) verbal (qawlan ma'rufa, qawlan baligha, qawlan maysura, qawlan layina, qaulan karima, qawlan sadida, qawlan tsakila, and qawlan adhima) and b) nonverbal (facial/expression (ghadul bashar), proxemic (ikhtilat, 'ijtima, nfishal), kinesthetic (khithab), artificial/performance (tabaruj), touch sensitivity, and others This study has the same views as: al-Maraghi, as-Suyuthi, al-Zuhaili, Wadud, Umar, Hamka, Shihab and others who revealed that potential differences in several types of verbal and nonverbal humans determine differences in communication gender, but in position, position, and role do not have differences intellectually, emotionally, and transcendentally.